The Impact of the Implementation of Complete Systematic Land Registration on Legal Certainty in the Registration of Land Ownership Rights in Indonesia - Krismantoro, Damianus; Hutapea, Maria; Joe, Christian (Westscience Press, 2024)
The establishment of legal certainty is one of the goals of land registration. Both Article 19 of the UUPA and Article 3 of Government Regulation No. 24 of 1997 on Land Registration support this. Both methodical and haphazard land registration may lead to legal certainty in the form of certificates. Initiated in 2016, the Complete Systematic Land Registration Program is still running. The Impact of Complete Systematic Land Registration Implementation on Legal Certainty in the Registration of Property Rights in Indonesia is the title of this study. The purpose of this study is to look at how Complete Systematic Land Registration could affect Indonesia's property rights registration system's legal certainty. Normative legal research employing secondary data is what this work does. According to a 2024 study, the National Land Agency, the government, saw both good and negative effects from the implementation of Complete Systematic Land Registration, in addition to benefits for participating landowners.